2022
DOI: 10.3389/fmed.2022.892831
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Inducible Protein, but Not Prolactin, Is Present in Human Tears, Is Involved in Tear Film Quality, and Influences Evaporative Dry Eye Disease

Abstract: PurposeDecreased production of the aqueous component of the tear film is an important cause of the development of dry eye disease (DED). Tear production is influenced by hormones and hormone-like factors. Prolactin (PLR), a multifunctional pituitary gland hormone, is regularly present in the lacrimal gland of rats and rabbits. In humans, serum PLR concentration correlates with tear quality. To gain deeper insights of possible effects of PRL, prolactin receptor (PRLR) and prolactin inducible protein (PIP), we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…After assessing the quantity of tears, we used sensitive untargeted mass spectrometry to analyse the tear proteome quality. Among the identified proteins, we detected factors known to be present in tears, such as lactotransferrin 26 , serum albumin 27 , prolactin inducing protein 28 , peroxiredoxin 6 and gelsolin 29 , confirming the efficiency of the proteomic analysis. Similarly to the tear production, the proteomic signature was almost not altered in the context of OPA1 mutation, regardless of the animal age (Fig.1B).…”
Section: Resultssupporting
confidence: 60%
“…After assessing the quantity of tears, we used sensitive untargeted mass spectrometry to analyse the tear proteome quality. Among the identified proteins, we detected factors known to be present in tears, such as lactotransferrin 26 , serum albumin 27 , prolactin inducing protein 28 , peroxiredoxin 6 and gelsolin 29 , confirming the efficiency of the proteomic analysis. Similarly to the tear production, the proteomic signature was almost not altered in the context of OPA1 mutation, regardless of the animal age (Fig.1B).…”
Section: Resultssupporting
confidence: 60%
“…PIP is typically expressed in cells that possess apocrine properties, such as apocrine glands in various locations including the axilla, vulva, eyelid, ear canal, and seminal vesicle [ 13 ]. Additionally, PIP has been observed in serous cells of salivary glands, bronchial submucosal glands, and accessory lacrimal glands, which share some similarities with apocrine glands despite not being classified as typical apocrine epithelia [ 14 , 15 ]. As a secretory protein, PIP can be found in various bodily fluids such as seminal plasma, saliva, lacrimal fluid, tears, sweat gland secretion, amniotic fluid, and the blood of pregnant women [ 8 , 16 ].…”
Section: Pip: Structure Expression and Homeostatic Functionmentioning
confidence: 99%
“…The electrolytes in tears such as K + , Na + , Ca 2+ , Mg 2+ , and Cl − can be converted into blood electrolyte levels. For example, urea reflects the health of kidney function, glucose is present as an indicator of diabetes, various proteins are associated with diseases such as inflammation, AIDS, and cancer, and cortisol reflects the level of stress as some studies have shown a relationship between cortisol and diabetes [ 112 , 113 , 114 , 115 ].…”
Section: Wearable Biosensors Based On 2d Materialsmentioning
confidence: 99%